Liberty's chain : slavery, abolition, and the Jay family of New York - Gellman, David Nathaniel (Three Hills, an imprint of Cornell University Press, 2022)
"This book studies the Jay family's relationship to the institution of slavery, to enslaved people, and to the abolitionist movement in New York and the United States from 1685 to 1912" --